Past, present, and future perspectives of biodegradable films for soil: A 30-year systematic review - Sun, Yitao; Yang, Wenlong; Shi, Hongxia; Tanveer, Sikander Khan; Hai, Jiangbo (Frontiers in Bioengineering and Biotechnology, 2022)
Based on the Web of Science Core Collection (WOSCC) database, the academic works on biodegradable films for soil published in the past 30 years were analyzed. In order to ensure the rigor of this experiment, this paper is based on the mathematical double matrix model VOS Viewer software and CiteSpace software. This work shows that publications in biodegradable films for soil are on the rise; polymer science is the most popular discipline for soil biodegradable films; China and the United States are significant forces; Washington State University is the researcher's significant contributor. This study further identifies and reveals the essential characteristics, research strength, knowledge structure, main research fields, and research hotspots in the later stage of the field of biodegradable films for soi and introduces the Activity Index (AI) and the Attractive Index (AAI) to evaluate different countries trends and performance. This paper also further illustrates the importance of biodegradable films by introducing field experiments in which different plants use biodegradable films. Research in the field of biodegradable films for soil is divided into four main research areas and knowledge structures; future "the ecological and environmental protection of biodegradable films," "crop growth and development," and "research on soil traits" are likely to be of great interest to scholars. The study can be seen as a microcosm of the development of biodegradable films for soils, which will help researchers quickly identify their general patterns. Readers can better understand the changes and development trends in this field in the past 30 years and provide